Comparison of the efficacy of soaking and drying methods for the disinfection of handwashing sinks in ICU - Chen, Jieqiong; Chen, Yu; Xu, Xiaomin; Xu, Zhaojun; Tong, Chenxi (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the effects of drying, soaking, and two combined disinfection methods on the disinfection efficiency of ICU handwashing sinks.MethodsFrom January to June 2024, eight handwashing sinks in the ICU were randomly divided into control group (n = 2), soaking group (n = 2), drying group (n = 2), and combination group (n = 2). The control group wiped with quaternary ammonium wipes only; the soaking group used chlorine disinfectant for 30 min based on the control group; the drying group was dried in a dryer for 15 min based on the control group; and the combined group was a combination of soaking and drying. Samples were collected once a month to compare the ATP fluorescence values and bacterial detection rates. Fisher’s exact test was used to compare categorical variables, Kruskal-Wallis’s test was used to compare continuous variables. Dunn’s post-test was used for pairwise comparison between groups.ResultsThe study found that before disinfection, no significant differences in ATP levels were observed among the four groups (p = 0.615). After disinfection, significant differences emerged (p < 0.001, η2 = 0.225), with the combined group showing the lowest ATP values and highest pass rate (100%). Dunn’s post hoc tests revealed the combined group had significantly lower ATP values compared to other groups (p < 0.01, Cohen’s d > 1.369). Bacterial detection showed an overall rate of 22.92% (11/48), with Pseudomonas aeruginosa being the predominant pathogen (81.82%, 9/11). The combined group had no bacterial isolates, while other groups had varying levels of contamination.ConclusionOverall, all four methods in this study were found to be effective in disinfecting ICU handwashing sinks, but the combined method of soaking and drying was superior to the other three.